1988
DOI: 10.1159/000195530
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Center Output following Zopiclone or Diazepam Administration in Patients with Pulmonary Disease

Abstract: Mouth occlusion pressure at 0.1 s (P0.1) and minute ventilation (VE) were measured at rest and during progressive hypercapnia in 32 patients. Under double-blind conditions and according to a 2 × 2 Latin-square design, half the patients received one oral dose of diazepam and its placebo. Using the same design, the other half received zopiclone and its placebo. Normocapnic and moderately hypoxemic patients between the ages of 21 and 69 with moderate to severe chronic obstructive pulmonary disease were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 7 publications
2
19
0
1
Order By: Relevance
“…Our results are consistent with previous studies that have reported links with benzodiazepines and a variety of adverse respiratory physiology outcomes in COPD [6][7][8][9][10][11][12]. Benzodiazepines are also reported to decrease arousability in healthy individuals during sleep [29], which may prolong the duration of respiratory physiological abnormalities or contribute to aspiration.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with previous studies that have reported links with benzodiazepines and a variety of adverse respiratory physiology outcomes in COPD [6][7][8][9][10][11][12]. Benzodiazepines are also reported to decrease arousability in healthy individuals during sleep [29], which may prolong the duration of respiratory physiological abnormalities or contribute to aspiration.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a true relationship between benzodiazepine use and adverse respiratory outcomes in the older COPD population is supported by biological plausibility (benzodiazepine use is associated with negative respiratory physiology markers) [6][7][8][9][10][11][12].…”
Section: Copd | Nt Vozoris Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The most likely explanation for this reduction is a fall in resting ventilation. On the other hand, it has been demonstrated that zopiclone has no significant effects on control of breathing in patients with severe chronic obstructive pulmonary disease [17]. Nevertheless, in our seven other patients with UARS, none of the respiratory parameters were substantially affected by zopiclone ( figure 1).…”
Section: Discussionmentioning
confidence: 58%
“…Zopiclone is a short-acting cyclopyrrolone that appears to differ clinically from benzodiazepines in several ways: it preserves slow wave sleep (SWS) [14], it does not impair daytime performance in normal subjects [15,16], it has no significant effect on the control of breathing during quiet sleep, quiet wakefulness, or induced hyperventilation in patients with pulmonary disease [17], and it has only minimal deleterious effects on respiration in patients with OSAS [18].…”
mentioning
confidence: 99%